One night, while I was on duty a poor man entered in to my duty room - Khan, Md Masudur Rahman (Bangladesh Medical Journal, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/bmj.v43i1.21381 Bangladesh Med J. 2014 January; 43 (1): 56